What Do Reflective Essays Tell Us About Student Learning Outcomes From Inquiry- and/or Design-Based International Engagement Projects? - Kisaalita, William S.; Mativo, John; Youngblood, Kathryn M. (Journal of Community Engagement and Scholarship, 2022)
International inquiry-and/or design-based projects are increasingly recognized as a high-impact teaching and learning approach. However, if not incorporated well into STEM curricula, such as ABET-accredited engineering degrees, they may result in more time to graduation. A popular approach is to incorporate these experiences in capstone design-project courses, but assessment of the international activity learning outcomes can be challenging. The objective of this study was to assess if open-ended student reflections can serve as an assessment tool that allows instructors to capture the rich and complex outcomes of international project-based design activities. Qualitative methods (NVivo and BEVI) were used. In the NVivo approach, emergent themes were identified from 45 reflections authored by students who conducted international inquiry-and/or design-based engagement projects. Students’ trips to their respective locations lasted between 2 and 8 weeks. In the BEVI approach, a longitudinal follow-up survey was administered 5 or more years after graduation. Reflective essays captured a wide spectrum of student learning outcomes gained from project-based learning (mostly knowledge and skills) and service-learning (mostly attitude and identity) and can thus be used as a sole assessment tool. Outcomes of international project-based service-learning include not only developing an empathetic attitude but also moving to action consistent with the aroused empathetic feelings and thoughts. Five or more years after graduation, the empathy observed soon after the international project can still be found in former students.